Preparation And Characterization Of Calcium Copper Titanate Filled Epoxy Composites For Embedded Capacitor Applications - Dandan Satia, Mohd saidina (2015)

(untitled)
Continuous miniaturization of electronic devices result in a high demand of embedded capacitor that offers significant reduction in size, better dielectric and thermal performance, reliability and lower cost. Polymer-ceramic composites have been considered as the most suitable dielectric materials for embedded capacitor. In this study, ceramics such as calcium copper titanate, CaCu3Ti4O12 (CCTO) and barium titanate (BaTiO3) were used as fillers in epoxy thin film composites. The properties of epoxy thin film composites fabricated based on different filler loading (5 to 20 vol%), fabrication methods such as spin coating (SC) and hot press (HP) methods, hybrid fillers (CCTO and BaTiO3), surface treatment of filler and various types of epoxy resins (DER 332, Epolam 2015 and OP 392) were characterized. Results showed that CCTO/epoxy composite exhibited higher dielectric constant, Tg and thermal conductivity compared to those of unfilled epoxy and BaTiO3/epoxy composites. In the second series, CCTO filler filled epoxy composite was chosen for further investigation. CCTO/epoxy composite with filler loading of up to 40 vol% was able to be produced by using HP method. It was found that 40 vol% CCTO/epoxy (HP) composite has increased 55% of dielectric constant and 83% of storage modulus, and decreased 69% of CTE compared to 20 vol% CCTO/epoxy (SC) composite. Hybrid fillers composites were fabricated and results indicated that Hybrid 70:30 showed positive hybrid effect compared to those of single filler composites; CCTO/epoxy and BaTiO3/epoxy thin film composites. After treatment of CCTO by silane-based coupling agent, sample with 10% treated CCTO filled epoxy composite presented remarkable improvement with an increased 60% of dielectric constant than untreated CCTO/epoxy thin film composite. Based on various epoxy resins, treated CCTO/OP 392 epoxy thin film composite has improved 10% of dielectric constant and decreased 38% of CTE compared to 3M Embedded Capacitor. In short, treated CCTO filled OP 392 epoxy thin film composite exhibited good dielectric properties and thermal properties compared to those of untreated CCTO composites, hybrid fillers composites and other treated composites.